The importance of a Biosphere Reserve of Atlantic Forest for the conservation of stream fauna - Yoshida, Claudia Eiko; Uieda, Virginia Sanches [UNESP] (Int Inst Ecology, 2014)
Preservation of terrestrial fauna and flora has been the main reason for the settlement of most protected areas in the past 30 years, but although those areas may include water bodies, this does not necessarily mean that the biodiversity of freshwater environments are also protected. In the present study, the fauna inventory of eight streams (1st, 2nd, 4th and 5th orders) of three microbasins of Japi Mountain, a Biosphere Reserve of Atlantic Forest recognised by UNESCO since 1994, located in S (a) over tildeo Paulo state, southeast of Brazil, was conducted. The hypothesis of this study is that the conservation of this area is important for the maintenance of the aquatic biodiversity of this biome, and so, this world hotspot deserves priority conservation actions. From 2005 to 2007, benthic macroinvertebrates, fishes and, eventually, anuran amphibians were sampled in these streams. The results showed that Japi Mountain contributes to the conservation of 138 taxonomic units of the aquatic biota and covers a rich and representative biodiversity of freshwater fauna of the world (0.2%), Neotropical region (0.9%), Brazil (2.4%) and S (a) over tildeo Paulo state (17.9%). The studied streams in the Environmental Protection Area help protect endangered taxa like the fishes Neoplecostomus paranensis and Pareiorhina cf rudolphi, and shelter freshwater invertebrates and fishes whose distribution is restricted to the Brazilian territory. Japi Mountain is also an important haven of species that was missing there like the frog species Vitreorana eurygnatha. Thus, this species inventory emphasises the importance of conservation actions of the freshwater environments of this Biosphere Reserve of Atlantic Forest.

A conservação da fauna e flora terrestres tem sido a principal razão para o estabelecimento da maioria das áreas protegidas nos últimos 30 anos, porém, apesar de muitas destas áreas apresentarem corpos d’água, isto não significa necessariamente que a biodiversidade dos ambientes dulcícolas também estará protegida. No presente trabalho foi realizado o levantamento da fauna de oito riachos (1ª, 2ª, 4ª e 5ª ordens) de três microbacias da Serra do Japi, localizada no estado de São Paulo e reconhecida como Reserva da Biosfera da Mata Atlântica pela UNESCO desde 1994. A hipótese do estudo é de que a conservação desta área seja de grande importância para a manutenção de sua biodiversidade aquática, comprovando assim a necessidade de ações prioritárias de conservação deste bioma. No período de 2005 a 2007 foram amostrados nestes riachos os macroinvertebrados bentônicos, peixes e, eventualmente, anfíbios anuros. Os resultados revelaram que a Serra do Japi contribui na conservação de 138 unidades taxonômicas da biota aquática e abriga rica e representativa biodiversidade da fauna de água doce do mundo (0,2%), da região neotropical (0,9%), do Brasil (2,4%) e do estado de São Paulo (17,9%). Os riachos das áreas de proteção ambiental estudados ajudam na proteção de táxons listados como vulneráveis a extinção no estado, como Neoplecostomus paranensis e Pareiorhina cf rudolphi, e abrigam animais dulcícolas de distribuição restrita ao território brasileiro. A Serra do Japi também constitui um importante reduto de espécies até então desaparecidas, como o anuro Vitreorana eurygnatha. Assim, este levantamento enfatizou a importância de ações de conservação dos ambientes aquáticos desta Reserva da Biosfera da Mata Atlântica.
A importância de uma Reserva da Biosfera da Mata Atlântica para a conservação da fauna de riachos
Keywords: Amphibians; Freshwater; Fish; Invertebrates; Protected areas; Anfíbios; Água doce; Peixes; Invertebrados; Áreas protegidas